How do I find the equivalent statement to the statement ~(p -> ~q)

  • Thread starter MiffedMFG1106St
  • Start date
  • Tags
    Equivalent
In summary: But if you negate the antecedent first, it becomes ~~p ^ ~~q.1] ~(p -> ~q)2] ~(~p v ~q)3] ~~p ^ ~~q4] p ^ qWhy does it not seem right to you?It does now, I wasn't paying attention to the rule of starting with the statement in parentheses first, the least dominant statement. Is that correct?BTW, thanks for the help so far.Well, people have different rules about parentheses, so I might not be following your rules. But they are just different ways of writing the same thing. I'm not
  • #1
MiffedMFG1106St
3
0
~(p -> ~q) <=> ? :confused:

I am having a heck of a time figuring this out, and I keep basically wanting to distribute the negation symbol to each individual simple statement in the conditional statement arriving at...

~[~(p -> ~q)] <=> ?
~(~p -> q) <=> ?
p -> ~q <=> ~p V ~q <=> ~(p ^ q)

But the book says I should come to p ^ q.

What am I doing wrong here. :confused:
 
Physics news on Phys.org
  • #2
Did you try changing the implication to a disjunction first, before distributing the negation?

1] ~(p -> ~q)
2] ~(~p v ~q)
3] ?
 
  • #3
honestrosewater said:
Did you try changing the implication to a disjunction first, before distributing the negation?

1] ~(p -> ~q)
2] ~(~p v ~q)
3] ?

Thanks for your reply honestrosewater.

Okay if I play that way

~(~p v ~q) <=> ~[~(p ^ q)] <=> p ^ q

Is that the correct process to acquire that answer then. First negate the antecedent and change the conditional to a disjunction. Then does the ~ distribute to both as in my answer above? Or am I going about this the wrong way? :confused:
 
  • #4
Sure, that is one way, if you have the rules to do that. You could also distribute the outer negation first and then drop the double negations.

1] ~(p -> ~q)
2] ~(~p v ~q)
3] ~~p ^ ~~q
4] p ^ q

Why does it not seem right to you?
 
  • #5
honestrosewater said:
Sure, that is one way, if you have the rules to do that. You could also distribute the outer negation first and then drop the double negations.

1] ~(p -> ~q)
2] ~(~p v ~q)
3] ~~p ^ ~~q
4] p ^ q

Why does it not seem right to you?

It does now, I wasn't paying attention to the rule of starting with the statement in parentheses first, the least dominant statement. Is that correct?

BTW, thanks for the help so far.
 
Last edited:
  • #6
Well, people have different rules about parentheses, so I might not be following your rules. But they are just different ways of writing the same thing. I'm not sure what rule you are talking about.

If I added back in parentheses around every single proposition, it would look like this:

1] (~((p) -> (~(q))))
2] (~((~(p)) v (~(q)))
3] ((~(~(p))) ^ (~(~(q))))
4] ((p) ^ (q))

Unless I missed some, haha.

There is often more than one way to prove something. In fact, there are often infinitely many ways, since, for one thing, you can just add in extra steps that don't do anything. So I wouldn't worry about finding the way or even the shortest or best way. If you find one way, it usually suggests other ways.

Why are you unsure about your equivalences? You can just check that each one is an instance of one of your rules, right?

You're very welcome. Welcome to PF, by the bye. :biggrin:
 
  • #7
MiffedMFG1106St said:
~(p -> ~q) <=> ? :confused:

I am having a heck of a time figuring this out, and I keep basically wanting to distribute the negation symbol to each individual simple statement in the conditional statement arriving at...

~[~(p -> ~q)] <=> ?
~(~p -> q) <=> ?
p -> ~q <=> ~p V ~q <=> ~(p ^ q)

But the book says I should come to p ^ q.

What am I doing wrong here. :confused:


There's an important eqivalence relation regarding negation of a conditional
(assuming a propositional logic).

~(p->q) <=> (p ^ ~q)

It's important because it's the first step in a proof by contradiction.
(In a predicate logic equipped with quantifiers (and most are)
life can be more difficult.)
In your problem, the result p ^ q is immediate from the above identity.
 

1. What is the equivalent statement to ~(p -> ~q)?

The equivalent statement to ~(p -> ~q) is p /\ q. This means that the original statement is equivalent to "p and q are both true."

2. How do I simplify ~(p -> ~q)?

To simplify ~(p -> ~q), you can use the De Morgan's law which states that ~(p -> q) is equivalent to p /\ q. Therefore, ~(p -> ~q) becomes p /\ q.

3. Can I use truth tables to find the equivalent statement to ~(p -> ~q)?

Yes, you can use truth tables to find the equivalent statement to ~(p -> ~q). By constructing a truth table for ~(p -> ~q), you will see that the statement is equivalent to p /\ q.

4. Is ~(p -> ~q) the same as ~(~p \/ q)?

Yes, ~(p -> ~q) and ~(~p \/ q) are equivalent statements. You can use the logical equivalence "p -> q" is equivalent to "~p \/ q" to see that these statements are the same.

5. How can I use logical equivalences to find the equivalent statement to ~(p -> ~q)?

You can use the logical equivalence "p -> q" is equivalent to "~p \/ q" and the De Morgan's law which states that ~(p \/ q) is equivalent to ~p /\ ~q to find the equivalent statement to ~(p -> ~q). Using these equivalences, you can see that ~(p -> ~q) is equivalent to p /\ q.

Similar threads

  • Set Theory, Logic, Probability, Statistics
Replies
3
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
3
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
16
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
4
Views
3K
  • Precalculus Mathematics Homework Help
Replies
5
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
16
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
12
Views
5K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
916
  • Set Theory, Logic, Probability, Statistics
Replies
4
Views
14K
Back
Top